Tumour endothelial cell reprogramming orchestrates angiocrine signalling to drive chemoresistance in breast cancer - Jesus Gomez-Escudero; Eleni Maniati; Julie Holdsworth; Gordon Beattie; Maruan Hijazi; Matt Guelbert; Samar Elorbany; Pedro Cutillas; Jun Wang; Kairbaan Hodivala-Dilke; Gabriela D’Amico (Angiogenesis, 2026)
Despite its established role in breast cancer treatment, Doxorubicin treatment remains subject to adaptive resistance mechanisms that extend beyond cancer cell intrinsic alterations ultimately reducing therapy efficacy. Our study in a MMTV-PyMT-driven mouse breast cancer model reveals that prolonged Doxorubicin (Dox) exposure triggers significant reprogramming of the tumour vasculature, substantially altering the angiocrine landscape and shaping treatment outcomes. Notably, tumours that initially respond, but later revert, display an endothelial cell subclustering with activation of proliferative and NF-κB-dependent cytokine pathways. We further identify a novel endothelial subpopulation characterised by higher expression of drug clearance and oxidative metabolism markers, suggesting an active role in mitigating Dox efficacy and angiogenesis promotion. These findings substantiate endothelial plasticity as a critical mediator of therapeutic failure. By uncovering these vascular adaptations, our work provides a new perspective on the underlying mechanisms of Dox resistance and the prolonged efficacy of chemotherapy in breast cancer.